Sustainability barriers and motivations in higher education: A students' perspective - Irina Maiorescu; Gabriel Cristian Sabou; Mihaela Bucur; Razvan Daniel Zota (Amfiteatru Economic Journal, 2020)
Today, more than ever, there is a need for sustainability and awareness of sustainable development importance in all sectors of activity. The Education for Sustainable Development (ESD) provided by higher education is vital for the sustainable transformation of society global strategy, because it moulds the social and professional behaviour of young people, with long-term beneficial effects on society and on environment. The current paper starts from an analysis of sustainable university and ESD challenges. Further on, it investigates, through the means of a quantitative research - online questionnaire based, the perception of students about ESD and other factors acting as barriers to sustainability, as well as their attitude and motivation for behaving sustainably within their university. The questionnaire was distributed between October-November 2019 to 292 students enrolled in the 2nd and 3rd year of Business and Tourism Faculty - Bucharest University of Economic Studies bachelor program, as well as to those students attending a master program within the same faculty. The results show that students see themselves - their lack of involvement, the main obstacle to the sustainable development of the university, rather than the absence of a university management strategy. The lack of a sustainability-oriented education within the university, both at the theoretical level, through the subjects of study, and at the practical level - through participation and example of the professors, is another barrier that can explain the low involvement of students in sustainable actions, in general. Information resulted from this research about students - important drivers of sustainability within university, may contribute to the successful planning of the transformation strategy and, on the long term, to a sustainable development of society.
Keywords: I23; Q56; 330; Sustainable university; sustainability barriers; students' motivation; Education for Sustainable Development (ESD)